Soft X-ray tomography illuminates drug-induced changes in insulin granules - Fuchs, Natalia; Weinhardt, Venera (Structure, 2025)
In this issue of Structure, Deshmukh et al.1 reveal that β cells actively remodel insulin secretory granules in response to specific physiological cues, altering granule density, proinsulin processing, and spatial distribution. This stimulus-specific structural maturation highlights how β cells sculpt their secretory machinery, offering new insights into insulin release regulation.
Online verfügbar 6 November 2025, Version des Artikels 6 November 2025
Gesehen am 20.02.2026